Development of an Automatic Adjustment System for Air-and-Screen Cleaning of a Modernized Combine Harvester - Pustovaya O.A.; Pustovoy E.A.; Usanov V.S.; Sakharov V.A.; Lipkan A.V.; Kotenko D.S. (BIO Web of Conferences)
The quality of grain separation in a combine harvester has the key role in increasing the efficiency of agricultural machinery use. The separation of grain and legumes should be effective and energy-efficient. One of the options to increase efficiency is to use automated air flow control systems. The use of digital control systems will help control the quality of the resulting grain and beans in real time, reduce damage, and enhance grain purity. To ensure control, we developed software and hardware meant to control the separation process in real time. The experiments show that, for high-quality separation, one has to maintain the air flow speed for soybeans at 8 m/s, for crushed grain – at 5 m/s, and for chaff and straw – at 2 m/s. These limitations were used to develop a software and hardware package that helps increase grain sorting efficiency.